PERBEDAAN KEMAMPUAN PEMECAHAN MASALAH FISIKA SISWA YANG DIAJAR DENGAN MENGGUNAKAN STRATEGI RECIPROCAL TEACHING DAN STRATEGI EKSPOSITORI PADA MATERI POKOK USAHA DAN ENERGI DI KELAS VIII SMP SWASTA TUNAS HARAPAN SAYURMATINGGI T.P. 2011/2012 - Mutiara Siagian (Jurnal Education and Development, 2017)
The result of preliminary study in eighth grade of SMP Swasta Tunas Harapan Sayurmatinggi shows that lack of using instructional variations causes student’s low achievement in solving physics problem in physics class. Based on that observation, this research is conducted to see the difference of student’s achievement in physics problem solving taught by using reciprocal teaching strategy and expository strategy. Quasi experiment is applied in this research. Population of this research is all students of eighth grade in SMP Swata Tunas Harapan. The sample is taken through cluster random sampling by taking 2 classes as sample; they are VIIIA as experimental class A and VIIIB as experimental class B. Each class consists of 30 students. The instrument used is achievement test of student’s physics problem solving which consists of 5 essay questions. The result of t-test shows that there is the difference between students’ achievement in physics problem solving taught by using reciprocal teaching strategy and expository strategy. The difference is that students’ achievement in physics problem solving taught by using reciprocal teaching strategy is higher than those taught by using expository strategy. Therefore, it can be concluded that there is the difference between between student’s achivivement in physics problem solving taught by using reciprocal teaching strategy and expository strategy in the topics of work and energy in eighth grade of SMP Swata Tunas Harapan Sayurmatinggi academic year 2011/2012.